Prevelance of Fabella: An MRI Study in The Eastern Anatolia Region of Turkey - Akdeniz, Huseyin; Ozkan, Sezai; Adanas, Cihan (Current Medical Imaging, 2021)
Background: The fabella, which is generally located in the lateral head of the gastrocnemius muscle, is a sesamoid bone that articulates with the posterior face of the lateral femoral condyle. As traditional information, the prevalence of fabella is between 10–30% in the population and is usually present in both knees. Introduction: The objective of this study was to investigate the knee MRIs in the Eastern Anatolia Region of Turkey subjects in order to assess the prevalence of the fabella and analyse the differences between gender, age and laterality and its symmetry pattern. Methods: This study was a retrospective study in patients older than 18 years whose knee MRIs were taken between February 2014 and February 2016. In this study, a total of 531 patients (290 females and 241 males) were included. The radiographs were examined by two orthopedic surgeons and the fabella was located. Later, an expert radiologist made the final decision and confirmed the results. Results: The number of patients included in the study was 531. We detected os fabella in 59 (11.1%) patients. Of the 59 os fabella, 33 were in the right knee and 26 were in the left knee, 38 were female and 21 were male. Conclusion: In this study, we investigated the age and gender differences besides the prevalence and the symmetry pattern of the fabella in the Eastern Anatolia Region of Turkey’s population. Prevalence of the fabella was found to be 11.1% which is different than previously published studies.
Keywords: knee